Prospects for a Common, Deregulated Nordic Electricity Market - Torstein Bye; Tor Arnt Johnsen (Statistics Norway, Research Department, 1995)
Electricity markets have typically been regulated all over the world. In Europe, UK and Norway have begun to deregulate their electricity markets. Several more countries will probably join them in the near future, for example Finland, Sweden and Spain. The objectives are twofold: to increase efficiency and to contribute both locally and globally to environmental improvement. Even larger regions like the European Union, plan to deregulate their internal electricity markets. For the EU this implies introduction of third party access to the transmission grid within and between the Union member countries. In this context, the Scandinavian push towards deregulation is an interesting experiment. We discuss the consequences of an international deregulation of electricity markets on the basis from simulations on an empirical energy market model for the Nordic countries. Deregulation may have severe effects on the location of new power plants within the Nordic area and implies a large impact on the income distribution both among countries and between electricity producers and consumers. The beneficial effects of deregulation are highly dependent upon the Nordic natural gas trade and prices. In our model, international co-ordination of environmental instruments like carbon dioxide taxes has a greater impact on emission level reductions than does deregulation. However, deregulation also contributes.
Keywords: E1; F1; Q4; H3; I3; 330; Deregulation; Electricity markets; Natural gas markets; CO2-taxes